2020
DOI: 10.1038/s41598-020-65820-5
|View full text |Cite
|
Sign up to set email alerts
|

Motor imagery training speeds up gait recovery and decreases the risk of falls in patients submitted to total knee arthroplasty

Abstract: With Motor imagery (MI), movements are mentally rehearsed without overt actions; this procedure has been adopted in motor rehabilitation, primarily in brain-damaged patients. Here we rather tested the clinical potentials of MI in purely orthopaedic patients who, by definition, should maximally benefit of mental exercises because of their intact brain. To this end we studied the recovery of gait after total knee arthroplasty and evaluated whether MI combined with physiotherapy could speed up the recovery of gai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(54 citation statements)
references
References 35 publications
(40 reference statements)
2
51
0
1
Order By: Relevance
“…In recent decades, MI has been made use of in several rehabilitative training procedures [ 41 , 42 ] with mixed results [ 43 ]. MI training has been also used with SCI patients with some success, suggesting its efficacy in motor recovery, for example in the rehabilitation of reach-to-grasp movements [ 44 ], improving wrist extensions [ 45 ], and, despite mixed results, in neuropathic pain reduction [ 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, MI has been made use of in several rehabilitative training procedures [ 41 , 42 ] with mixed results [ 43 ]. MI training has been also used with SCI patients with some success, suggesting its efficacy in motor recovery, for example in the rehabilitation of reach-to-grasp movements [ 44 ], improving wrist extensions [ 45 ], and, despite mixed results, in neuropathic pain reduction [ 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…Motor imagery training combined with other therapeutic interventions enhances the recovery of daily living activities in the elderly [17]. Zapparoli et al reported that the patient's damaged motor function was recovered by combining motor imagery training and physical therapy [18].…”
Section: Introductionmentioning
confidence: 99%
“…Core outcome sets are agreed minimum sets of outcomes that should be reported in research in a given topic area. 61 For each SoE assessment, we considered the number of studies, their designs and limitations (i.e., risk of bias and overall methodological quality), the directness of the evidence to the KQs (direct/indirect), the consistency (consistent/inconsistent) of study results, the precision (precise/imprecise) of any estimates of effect, the likelihood of reporting bias, other limitations, and the overall findings across studies. We also assessed the extent to which different (p)rehabilitation interventions were replicated within each KQ (replicated/not replicated interventions).…”
Section: Grading the Strength Of The Body Of Evidencementioning
confidence: 99%
“…Specific exercise components within rehabilitation goal components varied across programs. Nine studies included an adjunctive modality in combination with the rehabilitation program: two (Li 2014 andLi 2017) with the same adjunctive modalities delivered to both study arms and seven , Eymir 2020, Stevens-Lapsley 2012, Tsukada 2018, Jin 2018, Rockstroh 2010, Zapparoli 2020 where the added benefit of adjunctive therapy was the question of interest and the adjuvant modality varied between arms. The adjunctive modalities evaluated in these seven studies included neuromuscular electrical stimulation (NMES; n=3 RCTs); transcutaneous electrical nerve stimulation (TENS; n=1 RCT), biofeedback (n=1 RCT), motor imagery (n=1 RCT), and continuous passive motion (vs. active-heel slides which was the comparison of interest for this review) (n=1 RCT).…”
Section: Acute-phase Rehabilitationmentioning
confidence: 99%